Mała wielka kinematografia (Little Big Cinematography). Patrycjusz Pająk, Arcydzieła chorwackiego filmu fabularnego, Wydział Polonistyki Uniwersytetu Warszawskiego, Warszawa 2018, 395 s.. - Darasz, Zdzisław (Poznańskie Studia Slawistyczne, 2018)
In his book, Patrycjusz Pająk composes a Croatian film canon. His top list of the best Croatian feature films contains 15 pictures: Concert (1954) by Branko Belan, H–8... (1958) by Nikola Tanhofer, Train Without a Timetable (1959) by Veljko Bulajić, Rondo (1966) by Zvonimir Berković, The Birch Tree (1967) and Gold, Frankincense and Myrrh (1971) by Ante Babaja, Kaya (1967) and An Event (1969) by Vatroslav Mimica, Handcuffs (1969) by Krsto Papić, Occupation in 26 Pictures (1978) by Lordan Zafranović, The Rhythm of Crime (1981) by Zoran Tadić, The Melody Haunts My Memory (1981) by Rajko Grlić, What Iva Recorded (2005) by Tomislav Radić, Buick Riviera (2008) by Goran Rušinović, The Blacks (2009) by Goran Dević and Zvonimir Jurić. As a main criterion for building his own canon, the author takes the innovative character of the cinematic language and the rich symbolic imagery of the story.